Probiotics for oral health: a critical evaluation of bacterial strains - Beattie, Rachelle E. (Frontiers in Microbiology, 2024)
Oral health is critical for total body health and well-being; however, little improvement in oral health status has occurred in the U.S. over the past 20 years. Tooth decay and gum disease remain highly prevalent, with more than 90% and 50% of adults suffering from these conditions, respectively. To combat this lack of improvement, alternative approaches to dental care are now being suggested. One such alternative therapy is probiotics for oral care. In the oral cavity, probiotic strains have been shown to reduce levels of oral pathogens, inhibit the formation of dental caries, and reduce the levels of bacteria that cause halitosis. However, as the oral care probiotic market expands, many products contain bacterial species and strains with no documented health benefits leading to confusion and mistrust among consumers and clinicians. This confusion is enhanced by the regulatory status of probiotic products which puts the onus of safety and efficacy on the manufacturer rather than a central regulatory body. The overarching goal of this review is to provide consumers and clinicians with documented evidence supporting (or refuting) the health benefits of oral care probiotics marketed for sale in the United States. This includes defining what constitutes an oral care probiotic product and a strain level analysis of candidate probiotics from the genera Streptococcus, Lactobacillus, Bifidobacterium, and Bacillus. Additionally, prebiotics and postbiotics will be discussed. Finally, a set of considerations for consumers and clinicians is provided to empower probiotic product decision making. Together, this review will improve understanding of oral care probiotics marketed in the US for dental professionals and consumers.